Taxonomic revision of the Savanna Nightjar (Caprimulgus affinis) complex based on vocalizations reveals three species - George Sangster; Kim Manzon Cancino; Robert O. Hutchinson (Avian Research, 2021)
Abstract Background The Savanna Nightjar (Caprimulgus affinis) is a widespread, polytypic species which was previously treated as two or three species. It is currently treated as a single species based on superficial similarity of their songs but no detailed comparisons of the songs in this complex have been made. Methods A total of 15 acoustic variables were measured for the songs of 86 individuals representing 8 of the 10 subspecies in the complex. Results Three major groups can be distinguished based on univariate and multivariate analyses: a northern group consisting of the subspecies C. a. monticolus, C. a. amoyensis and C. a. stictomus; a southern group consisting of C. a. affinis, C. a. kasuidori, C. a. timorensis and C. a. propinquus; and a third group in the Philippines consisting of C. a. griseatus. Conclusions It is here argued that these groups are best treated as species, and that Franklin’s Nightjar (C. monticolus) and Kayumanggi Nightjar (C. griseatus) are reinstated as separate species.